Meningkatkan Kreativitas Anak Usia Dini melalui Kegiatan Kolase di RA Yaa Bunayya Desa Mompang Julu - Soraya Hasyim Hasibuan; Annisa Wahyuni; Hanifah Oktarina (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research aims to increase the creativity of early childhood through collage activities at RA Yaa Bunayya, Mompang Julu Village. The method used was Classroom Action Research (PTK) with group B research subjects consisting of 10 students. Data collection was carried out through observation sheets and documentation, with a focus on aspects of fluency, flexibility, originality and creative development. The research results show that collage activities can increase children's creativity. In cycle I, 20% of children showed very good development, 50% were as expected, 20% were starting to develop, and 10% were not yet developing. In cycle II, there was a significant increase, with 70% of children developing very well, 20% as expected, and 10% starting to develop. These findings indicate that collage not only improves children's fine motor skills, but also encourages their creative expression. Therefore, it is recommended that collage activities be used as a learning method that is routinely implemented in early childhood education. It is hoped that this research can make a positive contribution to the development of children's creativity and become a reference for educators in optimizing learning.